Molecular Evidence for Extrapair Paternity and Female-Female Pairs in Antarctic Petrels - Lorentsen, Svein-Håkon; Amundsen, Trond; Anthonisen, Kristin; Lifjeld, Jan T. (The Auk, 2000)
Considerable interspecific variation exists in the frequency of extrapair fertilizations (EPFs) in birds. In general, EPFs are more common and occur at higher frequencies in passerines than in nonpasserines (Westneat and Sherman 1997). Lower rates of EPFs are typical for territorial nonpasserines as well as those that breed colonially (Westneat and Sherman 1997). This seems to contradict Birkhead and Møller's (Birkhead and Møller 1992, Møller and Birkhead 1993) hypothesis of intense sperm competition in colonial birds. Their arguments were based on the assumption that the need for nest defense in dense aggregations restricts the ability of males to guard their mates, and that the high number of potential extrapair mates available in colonies selects for a high rate of extrapair copulations (EPCs). In contrast, Westneat and Sherman (1997) found no correlation across species between the frequency of EPFs and nesting dispersion, local breeding density, or breeding synchrony, although EPFs were related to nesting density within species. This suggests that EPC rates are not informative regarding EPF rates in colonial birds (Westneat and Sherman 1997), or that the pattern reported by Møller and Birkhead (1993) does not hold true when more species are included. The conflicting evidence regarding the relationship between extrapair activities and breeding density calls for more empirical studies, especially among colonial nonpasserines. Social monogamy is the predominant mating system in the Procellariiformes (Warham 1990). Several aspects of their breeding biology may, however, provide favorable opportunities for extrapair sexual activity. First, colonial breeding provides ample opportunities for EPCs because many potential partners are available at close range (Birkhead and Møller 1992, Møller and Birkhead 1993). Second, when the sexes are spatially and/or temporally separated, as may be the case in procellariiforms where adults seek food far from the colony, males have few cues to assess whether their mates have been unfaithful. Hence, few reasons exist to expect a facultative decrease in male parental investment if cuckolded, in contrast to the case for many territorial species where a male may have more reliable cues to his mate's unfaithfulness (e.g. female disappearance, high intrusion rate, etc.). Accordingly, colonial breeding may facilitate EPCs for both sexes, and colonial species may be expected to display high rates of EPC. Paternity studies require error-free sex determination of adults. This is straightforward for clearly dimorphic species, or if sex determination can be done from genitalia during the fertile period. But if fieldwork can be performed only during the nestling period, sex determination may be problematic for largely monomorphic species, and indirect methods must be used. In the Antarctic Petrel (Thalassoica antarctica), the two sexes differ slightly in mean body size. Lorentsen and Røv (1994) used this difference to determine the sex of Antarctic Petrels by discriminant function analysis (DFA). The procedure correctly determined the sex of 92% of the birds in a sample from the same year. This does not necessarily imply a similar resolution if the discriminant function is adopted for samples from other years, or if data are collected by other observers. Moreover, although useful for many purposes, 92% resolution in sex determination is insufficient for paternity studies. Therefore, we performed molecular sexing of all breeding adults according to the PCR-based method of Griffiths et al. (1998). The main aim of our study was to analyze whether extrapair paternity occurs in a colonial procellariiform, the Antarctic Petrel. We also tested the robustness of morphological sex determination (from DFA) across seasons relative to that obtained from molecular techniques.
Keywords: Dronning Maud Land; NARE 1993/94; fugler; ornitologi; petreller; zoologi

Diet and prey consumption of Antarctic petrels Thalassoica antarctica at Svarthamaren, Dronning Maud Land, and at sea outside the colony - Lorentsen, Svein-Håkon; Klages, Norbert; Røv, Nils (Polar Biology, 1998)
The diet of the Antarctic petrel Thalassoica antarctica was studied during two seasons at Svarthamaren, an inland colony in Dronning Maud Land, Antarctica, and in the pack ice off the coast of Svarthamaren. The most important food (wet mass) at Svarthamaren was crustaceans (67%), fish (29%) and squid (5%); however, individuals collected in the pack ice took mostly fish (87%). The prey composition and lengths of prey are comparable to what has been documented in other studies on this species. Estimates of food consumption by birds breeding at Svarthamaren (ca. 250,000 pairs) suggest that approximately 6500 tonnes of crustaceans, 2800 tonnes of fish and 435 tonnes of squid are consumed during the breeding season. The annual consumptions of these birds are estimated to be 34,100 tonnes of crustaceans, 14,700 tonnes of fish, and 2300 tonnes of squid. Satellite telemetry data indicate that Antarctic petrels from Svarthamaren may fly more than 3000 km during one foraging trip, and thus may cover a huge ocean area to obtain their prey.
Keywords: Dronning Maud Land; NARE 1991/92; NARE 1993/94; fugler; ornitologi; petreller; zoologi

Melting, runoff and the formation of frozen lakes in a mixed snow and blue-ice field in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar; Elvehøy, Hallgeir; Bøggild, Carl Egede; Sand, Knut; Liston, Glen (Journal of Glaciology, 1996)
Large-scale melting phenomena such as meltwater drainage channels and meltwater accumulation basins of frozen lakes were surveyed on the land ice mass in Jutulgryta, Dronning Maud Land, Antarctica, during the Norwegian Antarctic Research Expedition in 1989–90 (NARE 1989–90). The largest frozen lake that was observed was close to 1 km in width. These melting features were also detected in a Landsat Thematic Mapper image recorded on 12 February 1990. Then, during NARE 1993–94, a 5year glaciological programme was started in this area. In spite of negative air temperatures and the presence of a frozen ice surface, sub-surface melting and runoff were found within the uppermost metre in blue-ice fields. The sub-surface melting is a consequence of solar radiative penetration and absorption within the ice, i.e. the “solid-state-greenhouse effect”. Temperatures in blue ice were about 6°C higher than for snow. Internal melt and meltwater transport were observed throughout the 1 month of measurements. The conditions for active melting in Jutulgryta are probably marginal. A slight increase of air temperatures can result in more “classical” surface melting, whereas a cooling may disable sub-surface melting. Studies of how the extent and characteristics of the melting features change with time can be particularly valuable as indicators of climate change. This ongoing programme clearly identifies the importance of analyzing how these melting features originate, of mapping their present areal distribution, of determining how sensitive they are to climate change and of Studying changes in the past and possible changes in the future.
Keywords: Dronning Maud Land; NARE 1989/90; NARE 1993/94; blåis; fjernanalyse; glasiologi; klimaendringer; satellitteknologi

Sub-surface melting in blue-ice fields in Dronning Maud Land, Antarctica: observations and modelling - Bøggild, Carl Egede; Winther, Jan-Gunnar; Sand, Knut; Elvehøy, Hallgeir (Annals of Glaciology, 1995)
Keywords: Dronning Maud Land; NARE 1993/94; glasiologi; observasjoner